FRI0133 Serum Levels of TNF Antagonists in Rheumatoid Arthritis: Can we Establish an Optimal Cut-Off to Identify Patients in Remission or Low Disease Activity?. (9th June 2015) - Sanmarti, R.; Inciarte-Mundo, J.; Estrada Alarcόn, P.; García Manrique, M.; Narvaez, J.; Rodríguez, J.; Gόmez Centeno, T.; Pascal, M.; Yagüe, J.
Abstract : Background: TNF antagonists (TNFα) are efficacious in controlling the signs and symptoms of rheumatoid arthritis (RA). Studies show low serum trough levels (STL) of TNFα are associated with worse therapeutic response. Objectives: To determine STL of adalimumab (ADA) and etanercept (ETN) in RA patients and establish a cut-off to discriminate remission or low disease activity. Methods: Cross-sectional study of 91 patients from the prospective multicenter INMUNOREMAR study, a cohort (all with DAS28 ≤3.2 at baseline) and 36 patients in whom immunogenicity was assessed due to active disease (all DAS28 >3.2) treated with ADA and ETN. Anti-drug antibodies (Abs) and STL were measured using Promonitor (Progenika Biopharma, Spain) ELISA kits. STL were compared by disease activity (Mann Whitney U test), and correlations between STL and DAS28 were analyzed (Spearman test). The accuracy and discriminatory capacity of ADA and ETN STL were assessed by ROC curves (AUC) for remission (DAS28≤2.6) and low disease activity (DAS28≤3.2). Results: 127 patients (81.9% female, median age 61 years, median disease duration 13 years, TNF therapy 60 months, 57 patients receiving ADA and 73 ETN, 29.9% of patients on monotherapy and 27.6% on low doses of biological treatment) were included. 55.9% of patients were in remission and 71.7% in remission/low activity (DAS28≤3.2). Four ADA patients developed anti-drug antibodies. STL of ADA and ETN were significantly higher in patients in remission than in those not in remission (median (P25-P75) ADA. 6.9 (2.7-12) vs. 0.5 (0.1-1) p<0.001 ETN 2.3 (1.5- 3.1) vs. 0.8 (0.4-1.8) p<0.001). Similar results were obtained when comparing remission/low disease activity with patients with DAS28 >3.2. A significant inverse correlation was observed between STL and DAS28 (ADA: rho =0.5 p<0.0001, ETN rho =0.37 p<0.001). Accuracy analysis with remission by DAS28 as the reference variable showed an AUC for ADA of 0.81 (95% CI 0.68-0.94), (s): 81.9%, (e): 81% and ETN of 0.747 (95% CI 0.68 to 0.85) (s): 71.1% (e) 71.4%. The STL with the greatest discriminative capacity for remission were 1, 336 μg/mL for ADA and 1.56 μg/mL for ETN. Remission/low disease activity by DAS28 as the reference variable showed an AUC for ADA 0.863 (95% CI 0.73 to 0.99) (s): 78.9% (e): 93.8% and ETN 0.876 (0.80 to 0.95) (s): 81.1% (e): 80%. The cutoffs for remission/low activity (DAS28≤3.2) were: ADA 1, 336 μg/mL and ETN 1.073 μg/mL. Conclusions: RA patients in remission/low disease activity showed higher ADA and ETN STL compared to those with active disease. Cut-off values with a high discriminative capacity to identify remission or low disease activity were established. References: Chen DY, Chen YM, Tsai WC, et al. Significant associations of antidrug antibody levels with serum drug trough levels and therapeutic response of adalimumab and etanercept treatment in rheumatoid arthritis.Ann Rheum Dis. 2014 Jan 17. doi: 10.1136/annrheumdis-2013-203893. Disclosure of Interest: None declared